Second Corinthians in the perspective of late second temple Judaism - Bieringer, Reimund (Compendia rerum Iudaicarum ad Novum Testamentum 1877-4970, 2014)
Front Matter -- Copyright Page -- Foreword -- Notes on Contributors -- Introductory Essay /Peter J. Tomson -- Love as that which Binds Everything Together?The Unity of 2 Corinthians Revisited in Light of Αγαπ- Terminology /Reimund Bieringer -- The Politics of the Fifties: Jewish Leadership and the Jews of Corinth in the Time of 2 Corinthians /Martin Goodman -- Methodological Remarks on ‘Jewish’ Identity: Jews, Jewish Christians and Prolegomena on Pauline Judaism /Joshua Schwartz -- The Notion of a ‘New Covenant’ in 2 Corinthians 3: Its Function in Paul’s Argument and Its Jewish Background /Friedrich Avemarie -- Christ, Belial, and Women: 2 Cor 6:14–7:1 Compared with Ancient Judaism and with the Pauline Corpus /Peter J. Tomson -- Paul’s ‘Collection for the Saints’ (2 Cor 8–9) and Financial Support of Leaders in Early Christianity and Judaism /Ze’ev Safrai and Peter J. Tomson -- Paul’s ‘Fool’s Speech’ (2 Cor 11:16–32) in the Context of Ancient Jewish and Graeco-Roman Culture /Catherine Hezser -- The Ascent into Paradise (2 Cor 12:1–12): Paul’s Merkava Vision and Apostolic Call /Christopher R.A. Morray-Jones -- Back Matter -- Bibliographical Abbreviations -- Bibliography -- Index of Names -- Source Abbreviations -- Index of Ancient Sources.